Paradigma Historis Backpacking Travel Sebagai Perjalanan Wisata - Pitaya Pitaya; Muhammad Baiquni; Marsono Marsono; Nopirin Nopirin (Jurnal Pariwisata Terapan, 2019)
Nowadays backpacking travel is the most popular travelling style which famous to the youth traveller. According to the history, the travelling style can be tracked from the nomadic tribes in all corner of the world for their moving habit for run their life. Through the ages, the nomad who carries backpack at their back to bring necessities adopted by soldiers, explorers, and many kinds of travellers, until transformed to the modern free independent tourist (FIT) ; backpacker, flash packer to the present techno packer. The backpackers itself always become an interesting object for the scholars and the tourism experts. Their travelling style colorized every great journey that men ever made.  This paper aim is to seek and identify the existence of backpackers and their travelling style throughout historical paradigm. The methods using in this research is both literatures studies and field observatory to the iconic backpacking travels sites in the history. The results show that the backpackers and backpacking travel consists of unique characteristics who determine their travelling style that different among the common tourist or even the group inclusive tour (GIT). The backpackers travels much longer, more far, they travel some time to the off beaten tracks, they always made interaction with the local community, and their journeys inspired others. No wonder if in the future backpacking travel will contributes so many influences to the tourism world.